TEACHERS' PROBLEMS IN THE UTILIZATION OF INSTRUCTIONAL MEDIA IN ENGLISH TEACHING:A CASE STUDY TOWARD ENGLISH TEACHERS IN THREE SENIOR HIGH SCHOOLS IN SUMEDANG - Mutiar Putri Dewi, - (2009)
ABSTRACT The study is entitled "Teachers' Problems in the Utilization of Instructional Media in English Teaching". It aims at identifying problems encountered by the English teachers in the utilization of instructional media and strategies used in handling the problems. It was conducted by using case study design in which the data were collected through interview and class observation. Nine English teachers from three senior high schools in Sumedang were involved in this study. The result of the study indicated that problems encountered were personal, institutional, and technical problems. The strategies to handle the problems were improving teachers' awareness and holding training, completing media, and asking capable person or employing alternative medium. The study indicates that there are problems encountered in media utilization particularly in technical media utilization. Thus, related parties should do considerable efforts to overcome those problems.